Microstructure Investigation of 13Cr-2Mo ODS Steel Components Obtained by High Voltage Electric Discharge Compaction Technique - Bogachev I. A. Igor Aleksandrovich; Yudin A. V. Artem Viktorovich; Grigorjev E. G. Evgeny Grigorjevich; Chernov I. I. Ivan Iljich; Staltsov M. S. Maxim Sergeevich; Khasanov O. L. Oleg Leonidovich; Olevsky E. A. Evgeny Aleksandrovich (Manufacturing Processes and Systems, 2015)
Title screen